2007
DOI: 10.3354/cr034119
|View full text |Cite
|
Sign up to set email alerts
|

Global diarrhoea morbidity, weather and climate

Abstract: Diarrhoea rates are influenced by weather and climate; transmission can be affected by temperature and rainfall extremes, although few studies have quantified this effect. We undertook a global cross-sectional study of diarrhoea incidence in children under 5, drawing on studies published in the last 50 yr, and assessed the association with climate variables. Log-linear regression was used to quantify any association, controlling for the effects of age, socio-economic conditions and access to improved water and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 15 publications
1
29
1
Order By: Relevance
“…Nevertheless, in contrast to the findings regarding the relationship between heavy rainfall and diarrhoea, which have been demonstrated in the majority of studies, the relationship between temperature and diarrhoea is not fully understood. A recent study conducted on a global scale (Lloyd et al 2007) found no association between average temperature and diarrhoea morbidity. Three influencing factors for this finding were considered by the author: (i) the study used the allcause diarrhoea in a broad range of sites, resulting in quite different pathogen profiles; (ii) the range of temperatures in the study sites, which did not have cool weather, was too narrow to allow differences to be detected and (iii) uncontrolled biases might have obscured an association.…”
Section: Discussionmentioning
confidence: 96%
“…Nevertheless, in contrast to the findings regarding the relationship between heavy rainfall and diarrhoea, which have been demonstrated in the majority of studies, the relationship between temperature and diarrhoea is not fully understood. A recent study conducted on a global scale (Lloyd et al 2007) found no association between average temperature and diarrhoea morbidity. Three influencing factors for this finding were considered by the author: (i) the study used the allcause diarrhoea in a broad range of sites, resulting in quite different pathogen profiles; (ii) the range of temperatures in the study sites, which did not have cool weather, was too narrow to allow differences to be detected and (iii) uncontrolled biases might have obscured an association.…”
Section: Discussionmentioning
confidence: 96%
“…86,87 Heat waves: A growing literature focuses on the health problems arising from heat waves in urban areas, with recent work considering the implications in lowincome urban settings. 82,[88][89][90][91] One study examined the history of heat wave-related deaths in three cites of contrasting wealth (gross national income per capita)-Delhi, India; London, England; and São Paulo, Brazil-based on daily counts of all-cause mortality (excluding violent deaths) using counts of deaths by age and cause derived from mortality registries for the four-year period of January 1991 to December 1994. Setting these data against time series data of daily ambient temperature, they found that for each of these cities, an increase in all-cause mortality was observed for same day and previous day temperatures 920°C, with the excess mortality being greatest in Delhi and smallest in London.…”
Section: Part Iii: Indicators For Urban Health Metricsmentioning
confidence: 99%
“…A multitude of studies have assessed the influence of weather conditions on human mortality or morbidity for chronic or infectious diseases [1,2,3,4,5]. However, few weather-health-related studies were found that have a focus on weather-related accidental casualties, which seem to happen unintentionally or from certain direct causes, such as traffic injury, assaults, or trauma.…”
Section: Introductionmentioning
confidence: 99%